Hnací ústrojí závodního Wankelova rotačního motoru - Blažo, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Hlavným cieľom diplomovej práce bolo spracovať základný návrh a konštrukčné riešenie hnacieho ústrojenstva Wankelovho rotačného motoru o výkone 300 kW pri otáčkach n = 9000 1/min. Na základe týchto údajov boli navrhnuté základné parametre motoru, návrh excentrického hriadeľa a komory. U excentrického hriadeľa bola na základe priebehu indikátorového diagramu spravená pevnostná analýza a analýza torzného kmitania.

The main aim of master’s thesis was to handle the computing proposal and the construction design of the powertrain of racing Wankel rotary engine with 300 kW power output and in the case of 9000 speed per minute. On the basic of these values was made the primary design of the rotary engine, design of the eccentric shaft and rotor housing. Mechanical stress and torsional vibrations of the eccentric shaft were analyzed by using the course of indicator diagram.
Powertrain of racing Wankel rotary combustion engine.
Keywords: Wankel; rotačný motor; excentrická hriadeľ; komora rotoru; pevnostná analýza; torzné kmitanie; trochoida.; Wankel; rotary engine; eccentric shaft; stress analysis; rotor housing; torsional vibrations; trochoid